2016
DOI: 10.1007/s00381-016-3250-8
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous extrapedicular vertebroplasty with expandable intravertebral implant in compression vertebral body fracture in pediatric patient—technical note

Abstract: PurposeThe aim of the article is to present the new extrapedicular percutaneous technique for posttraumatic vertebral column fracture.MethodsA 15-year-old boy needed a surgical Th8 posttraumatic vertebral body (VB) compressive fracture reduction due to insufficient conservative treatment and consistent severe clinical symptoms. After 6 months of external Jevett long-roll brace stabilization, progressive sagittal balance disturbance of thoracic kyphosis was measured and persistent clinical symptoms were observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Extrapedicular PVP (PKP) was 1st used in the upper and midthoracic vertebrae and was gradually applied to the lower thoracic and lumbar vertebrae. [16,17,18] The primary advantages of extrapedicular PVP (PKP) are that the puncture needle can easily reach the anterior-middle 1/3 point on the middle line of the vertebral body for PVP and easily reach the middle point on the middle line of the vertebral body for PKP. Additionally, bilateral puncture is not required, reducing the operative time and decreasing the radiation frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Extrapedicular PVP (PKP) was 1st used in the upper and midthoracic vertebrae and was gradually applied to the lower thoracic and lumbar vertebrae. [16,17,18] The primary advantages of extrapedicular PVP (PKP) are that the puncture needle can easily reach the anterior-middle 1/3 point on the middle line of the vertebral body for PVP and easily reach the middle point on the middle line of the vertebral body for PKP. Additionally, bilateral puncture is not required, reducing the operative time and decreasing the radiation frequency.…”
Section: Discussionmentioning
confidence: 99%
“…3 However, its success is somewhat limited because of pain arising from the loss of vertebral height in the later stages of the procedure; this also causes refracture of adjacent centrums, and it severely compromises patients’ quality of life. 4,5 Zoledronic acid, a novel drug used in the clinical treatment of osteoporosis, can accelerate fracture healing and reduce the refracture risk. Recent studies have suggested that statins can inhibit osteoclasts and promote osteogenesis.…”
Section: Introductionmentioning
confidence: 99%